2023
DOI: 10.7759/cureus.35421
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Abortion Attitudes in Medical Students After the Reversal of Roe v. Wade

Abstract: BackgroundOn June 24, 2022, the United States (U.S.) Supreme Court ruled in Dobbs v. Jackson Women's Health that the Constitution does not grant women the right to abortion. This new ruling may have a profound impact on not only the attitudes of medical trainees but the nature in which they are trained when it comes to abortion practices, indications, or procedures. Some clinics where medical schools provide first-hand abortion experience have closed. As a surge of extreme restrictions on abortion has been see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(93 reference statements)
1
1
0
Order By: Relevance
“…Religious affiliation in this sample was varied. Findings from this study found that lower levels of religiosity predicted more positive attitudes toward abortion (in general), findings which are supported by earlier literature [6][7][8][9]. About half of the participants reported religion was very important or somewhat important; the other half reported that it was not too important or not important at all (five participants declined to answer).…”
Section: Religiositysupporting
confidence: 88%
See 1 more Smart Citation
“…Religious affiliation in this sample was varied. Findings from this study found that lower levels of religiosity predicted more positive attitudes toward abortion (in general), findings which are supported by earlier literature [6][7][8][9]. About half of the participants reported religion was very important or somewhat important; the other half reported that it was not too important or not important at all (five participants declined to answer).…”
Section: Religiositysupporting
confidence: 88%
“…Religion and religiosity may influence one's attitudes toward abortion [6]. Research has shown that religiosity (i.e., the extent to which one participates in religious practices or customs), and religious affiliation can be a strong factor in predicting attitudes about abortion in medical students [7][8][9]. Medical students, not unlike physicians who identified as Catholic, Protestant, or Evangelical, generally opposed abortion, whereas students who identified as Jewish or non-religious were more likely to support abortion [8][9][10][11].…”
Section: Religiosity and Abortion: A Complex Intersectionmentioning
confidence: 99%